Morphometric and DNA Barcoding of endemic Halmaheran walking shark (Hemiscyllium halmahera, Allen, 2013) in North Maluku, Indonesia : Morphogenetic of endemic Halmaheran walking shark - Hawis MADDUPPA; ARINI S. P. PUTRI; RIDHO Z. WICAKSONO; BEGINER SUBHAN; NEBUCHADNEZZAR AKBAR; FIRDAUT ISMAIL; DONDY ARAFAT; DERTA PRABUNING; L.M. IQBAL MUKSIN; ENDANG S. SRIMARIANA; ABDURRACHMAN BAKSIR; DIETRIECH G. BENGEN (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Madduppa H, Putri ASP, Wicaksono RZ, Subhan B, Akbar N, Ismail F, Arafat D, Prabuning D, Sani LMI, Srimariana ES, Baksir A, Bengen DG. 2020. Morphometric and DNA Barcoding of endemic Halmaheran walking shark (Hemiscyllium halmahera, Allen, 2013) in North Maluku, Indonesia. Biodiversitas 21: 3331-3343. The walking shark (Hemiscyllium halmahera) commonly referred to as bamboo shark, is a shark species that belongs to the Hemiscyllidae family which is endemic in North Maluku, and Indonesian waters. These Hemiscyllium species are generally confined to the Australian-New Guinea region, save a specie which originates from Halmahera, an Indonesian island. Ever since its discovery, sufficient information on its existence has been largely unavailable. Hence, the purpose of this study is (1) to assess the morphology, using meristic measurements and length-weight relationship, and (2) to determine the molecular characteristics through DNA barcoding, phylogenetic reconstruction, and genetic diversity. The samples used in this research were obtained from Halmahera Archipelago, North Maluku, including Halmahera, Tidore, Ternate, Maitara, and Guraici in several expeditions between March 2017 and January 2018. 36 individuals in total were measured for morphometric parameters including Total Length (TL), Standard Length (SL), Head Length (HL), Body Circumference (BC), and Body Weight (BW). Out of a total of 36 sharks, tissue samples were obtained from 32 individuals for molecular identification. After the required measurements were obtained, all individuals sharks were released back to their habitat safely. Equations of linear regression were used to analyze the relationship between length and weight. Morphometric measurements indicated that the average total length of the walking shark samples obtained, were not more than 75± cm for both male and female specimens. The length-weight analysis revealed a positive allometric growth pattern in H. halmahera species, where weight was gained faster than an increase in length. The results of the DNA fragment length analysis from all samples were 793-bp. All 32 tissue samples identified as H. halmahera consisted of 3 samples from Ternate Island, 14 samples from Maitara Island, 9 samples from Guraici Island (South Halmahera), 10 samples from Central Halmahera, and 2 samples from Tidore Island. These results confirmed that DNA subsequence analysis indicates that H. halmahera is different from those sequences extracted from Genbank in the Australia-New Guinea region. This study successfully identified H. halmahera based on their morphological and molecular characters, and has therefore contributed to international genetic database (Barcoding Of Life Database-BOLD) for further studies.